Doping Efficiency in Cobalt-Doped ZnO Nanostructured Materials. (24th April 2019) - Kaphle, Amrit; Reed, Travis; Apblett, Allen; Hari, Parameswar
Abstract : Nanostructured ZnO thin films doped with cobalt from 5% to 20% were grown on glass substrates by a low-temperature chemical bath deposition (CBD) technique. We compared the doping efficiency of incorporating cobalt in ZnO nanostructured samples doped with cobalt via cobalt nitrate and cobalt chloride. The concentration of cobalt incorporated into the ZnO matrix was precisely determined using inductively coupled plasma mass spectroscopy (ICP-MS). Scanning electron microscopy (SEM) images showed that only at a 0.1 M ratio of the precursor solutions in CBD using cobalt nitrate as a dopant, the morphology of ZnO yielded hexagonally shaped nanorods. At a 1 M ratio of the precursor solutions, SEM images showed that the morphology of ZnO was nanoplatelets at all doping levels, irrespective of the doping method used. The synthesized nanostructures retained the wurtzite hexagonal structure only at 0.1 M precursor solution using cobalt nitrate doping, which was confirmed by X-ray diffraction (XRD) studies. In cobalt-doped samples using cobalt chloride as a dopant, XRD analysis confirmed the formation of a Simonkolleite structure. At 300°C, the Simonkolleite structure was converted to a wurtzite structure without changing the morphology. Electrical conductivity measurements at 300 K showed that ZnO nanorods doped with cobalt using cobalt nitrate yielded the lowest resistivity. The molarity of the precursor solution and dopant was found to have a substantial impact on the morphology and doping efficiency of the ZnO nanostructures.